Proceedings of the 2015 Annual Symposium on Computing for Development 2015
DOI: 10.1145/2830629.2830644
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Mobile Application Communication for Challenged Network Environments

Abstract: Designing mobile applications for challenged network environments necessitates new abstractions that target deployment architects, nondevelopers who are charged with adapting an ensemble of off-theshelf software to a deployment context. Data transfer is integral to mobile application design and deployments have inherent and contextual requirements that determine what data should be transferred and when. In this paper, we investigate building mobile applications in challenged network environments by focusing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…-To propose new tools compatible with the ODK suite or with the ODK-X suite [20], [21], [22], [23], [24]; -To make improvements to a single component of the ODK suite or the ODK-X suite, without having to touch all the others [25], [26]; -To use one or some of the components of the ODK or ODK-X suite without having to use the whole suite. The tools of the two suites can even be used with other technologies that do not belong to ODK [31], [32], [34], [38], [40], [41]; -To extend a component of the ODK or ODK-X suite by adding new functionalities and then to use this extension with the other components of the suite [27], [28], [29].…”
Section: Table-iii: Studied Articles By Themementioning
confidence: 99%
See 1 more Smart Citation
“…-To propose new tools compatible with the ODK suite or with the ODK-X suite [20], [21], [22], [23], [24]; -To make improvements to a single component of the ODK suite or the ODK-X suite, without having to touch all the others [25], [26]; -To use one or some of the components of the ODK or ODK-X suite without having to use the whole suite. The tools of the two suites can even be used with other technologies that do not belong to ODK [31], [32], [34], [38], [40], [41]; -To extend a component of the ODK or ODK-X suite by adding new functionalities and then to use this extension with the other components of the suite [27], [28], [29].…”
Section: Table-iii: Studied Articles By Themementioning
confidence: 99%
“…5 [20], [21], [22], [23], [24], [25], [26] Improvement or Creation of a new component of the ODK tool suite. 7 [27], [28], [29] Proposal for an ODK extension.…”
Section: Referencesmentioning
confidence: 99%
“…In practice according to the user studies, WiFi Direct seemed to be a preferable solution. WiFi Direct can take a bit longer to setup compared to Bluetooth, but offers better 4 Google Gears https://en.wikipedia.org/wiki/Gears_(software) (last accessed 10 May 2017) speeds and is particularly suitable for files more than 1MB in size as demonstrated by the authors. The authors have shown that Submit can act according to configured policies, for instance, it was able to conserve 3G traffic by sending only essential data, and the rest of the data was sent using WiFi.…”
Section: Group 3 Approaches On Personal Devicementioning
confidence: 94%
“…ODK Submit [4] targets the data collection and submission problem. ODK Submit uses contextually available information about the data (like the importance of the data, availability, and price of different types of network connection) to identify which channel should be used to transfer which type (or part) of the data.…”
Section: Group 3 Approaches On Personal Devicementioning
confidence: 99%
“…ODK takes a multi-perspective approach to the creation of customizable abstractions for varying contexts [10]. The platform perspective incorporates the device and operating system perspective on aspects such as connectivity, power, features, and mobility.…”
Section: Design Considerationsmentioning
confidence: 99%